Penerapan Model Pembelajaran Probing Promting Untuk Meningkatkan Pola Berpikir Kritis Peserta Didik Pada Mata Pelajaran Fikih Kelas VIII MTS Nurul Islam - Darmataksiah Darmataksiah; Satria Wiguna (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The learning process which is still teacher-centered causes students to be less active and less enthusiastic in the learning process, students are more silent and only listen to the explanations given by the teacher. The result is low student learning outcomes in Fiqh subjects and passive and inactive learning. Critical thinking is very important for student learning progress, especially in learning jurisprudence. Basically, fiqh lessons are fun learning, because they teach many things about everyday life based on concrete examples and how students can solve the problems they face. The importance of critical thinking for everyday life. This research uses the classroom action research (PTK) method. The subjects of this research are 19 students in class VIII of MTs Private Nurul Islam Paluh Dungun. Application of the probing promting learning model in Fiqh lessons about Prostration of Gratitude and Prostration of Tilawah for class VIII students at MTs Private Nurul Islam Paluh Dungun. Classroom action research carried out in Cycle I and Cycle II to apply the probing learning model in Fiqh lessons was proven to have improved students' critical thinking patterns and student learning outcomes. This can be seen from the results of the percentage of completeness of student learning outcomes in Cycle I, which was 63.15% and increased in Cycle II, namely 84.2%. So it can be concluded that the application of the probing learning model can improve students' critical thinking patterns in Fiqh lessons in class VIII MTs Private Nurul Islam Paluh Dungun.